THE DETERMINANTS OF DIVIDEND POLICY (An Empirical Study on Manufacturing Companies Registered in Indonesian Stock Exchange Period of 2016-2019) - lestari, nurni arrina (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
This research was aimed to analyze the factors that could affect company’s opportunities to distribute dividend, and based on those opportunities, this research would further identify the factors that could affect the size of dividend distributed by the company. The research sample was taken from manufacturing companies that have been registered in Indonesian Stock Exchange period of 2016-2019. The regression models were logistic regression which was used to analyze which variables that could affect the company’s opportunities in the dividend and multiple linear regression which was used to analyze which variables that could affect the size of distributed dividend. Furthermore, this research finding referred that the variables which could affect the company’s opportunities to distribute dividend were profitability, liquidity, and company’s size. From those three variables, the only variable of profitability which was able to affect the size of dividend that distributed by the company.